Occurrence of gastrointestinal parasites in local ducks at varying altitudes in Yogyakarta, Indonesia - Santika Anggrahini; Irkham Widiyono; Zein Ahmad Baihaqi; Ahmad Sofyan; Randi Mulianda; Wulandari Wulandari; Fitrine Ekawasti; Ima Fauziah; Sadarman Sadarman; Miarsono Sigit; Hendra Herdian; Riza Zainuddin Ahmad; et al. (Veterinary World)
Background and Aim: Gastrointestinal parasites are a common health concern in poultry, particularly in free-range farming systems. Local ducks (Anas platyrhynchos javanicus) in Indonesia are frequently exposed to various parasitic infections due to their extensive foraging behavior. Parasitic infections can reduce productivity, cause economic losses, and impact animal welfare. This study aimed to determine the occurrence of gastrointestinal parasites in ducks raised at different altitudes in Yogyakarta, Indonesia, and assess the influence of altitude and seasonal variation on infection rates.